Hubungan Kecerdasan Spiritual dengan Tingkat Kecemasan Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di Rumah Sakit Pertamina Bintang Amin Bandar Lampung - Mia Nurar Lina; Rika Yulendasari; Nirwanto Nirwanto (Malahayati Nursing Journal, 2024)
ABSTRACT Chronic kidney failure is a condition that slowly damages kidney function, resulting in the kidneys' inability to maintain fluid and electrolyte balance in the body. Patients with chronic illnesses generally have feelings of anxiety about their condition in the future. Many factors can influence anxiety in patients with chronic illnesses, one of which is spiritual intelligence. Spiritual intelligence is the intelligence to face and solve life's problems, namely the intelligence to place behavior and life in a broader life context. It is known that there is a relationship between spiritual intelligence and the level of anxiety in chronic kidney failure patients undergoing hemodialysis at Pertamina Bintang Amin Hospital, Bandar Lampung. The type of research used is quantitative. The design in this study used a cross-sectional approach. The population in this study were all chronic kidney failure patients undergoing hemodialysis at Pertamina Bintang Amin Hospital Bandar Lampung with a total of 104 respondents. The sampling technique in this research is Simple Random Sampling. This research proves that the majority of respondents (51.8%) have low spiritual intelligence and the majority of patients have severe levels of anxiety (33.7%) and very severe (33.7%), the results of the Chisquare test obtained a p-value 0.000 (0.05) which means there is a relationship between spiritual intelligence and the patient's anxiety level. Based on the results of the research, there is a relationship between spiritual intelligence and the anxiety level of chronic kidney failure patients undergoing hemodialysis at Pertamina Bintang Amin Hospital, Bandar Lampung City. Keywords: Spiritual intelligence, Anxiety Level, Chronic Kidney Failure.  ABSTRAK Gagal ginjal kronik adalah kondisi secara perlahan-lahan merusak fungsi ginjal, yang mengakibatkan ketidakmampuan ginjal untuk menjaga keseimbangan cairan dan elektrolit dalam tubuh. Pasien dengan penyakit kronik pada umumnya memiliki perasaan yang cemas akan kondisinya dikemudian hari, banyak faktor yang dapat mempengaruhi kecemasan pada pasien dengan penyakit kronik, salah satunya adalah kecerdasan spiritual. Kecerdasan spiritual adalah kecerdasan untuk menghadapi dan memecahkan masalah hidup, yaitu kecerdasan untuk menempatkan perilaku dan hidup dalam konteks hidup yang lebih luas. Diketahui hubungan kecerdasan spiritual dengan tingkat kecemasan pasien gagal ginjal kronik yang menjalani hemodialisa di Rumah Sakit Pertamina Bintang Amin Bandar Lampung. Jenis penelitian yang digunakan adalah kuantitatif. Rancangan dalam penelitian ini menggunakan pendekatan cross- sectional. Populasi dalam penelitian ini adalah seluruh pasien gagal ginjal kronik yang menjalani hemodialisa di Rumah Sakit Pertamina Bintang Amin Bandar Lampung dengan jumlah 104 responden. Teknik sampling dalam penelitian ini adalah Simple Random Sampling. Hasil dari penelitian maka ada hubungan antara kecerdasan spiritual dengan tingkat kecemasan pasien gagal ginjal kronik yang menjalani hemodialisa di Rumah Sakit Pertamina Bintang Amin Kota Bandar Lampung. Kata Kunci: Kecerdasan spiritual, Kecemasan, Gagal Ginjal Kronik.